Traité de l'harmonie universelle - Mersenne, Marin 1588-1648 (Paris Baudry, 1627)
This small treatise on Harmony represents the first two of the sixteen books planned for the treatise on Music, which Mersenne renounced. The work analyzes music in a philosophical and metaphysical way: theme of "Harmonia Mundi" drawn from Platonism, status of mathematics in the ideas of God, critical confrontation of Kepler and Fludd, examination of the Copernican hypothesis - all questions absent from the 'Harmonie universelle' of 1636.
dedicated to Monseigneur de Refuge, conseiller du roy
cited in Koopman 1985, pages 5, 13, 78, 94, 96-99
contains an inserted slip by TK with a question to Eline Holl
annotations in ink on title-page: "Collège ... [crossed through]; Mnsi. S. Germ. a pratis Cong. S. Maur 6 R 772"'
purchased from Librairie Alain Brieux, Paris
Keywords: 17th Century (1601-1700); Music theory; Musical analysis; Music philosophy and esthetics; France